Patterns and trends of Computed Tomography usage among pediatric and young adult patients in a private hospital in Rio de Janeiro, 2005-2015 - Tainá Olivieri Chaves; Ana Cristina Murta Dovales; Luiz Antônio Ribeiro da Rosa; Lene Holanda Sadler Veiga (Brazilian Journal of Radiation Sciences)
Computed tomography (CT) scanning is a relatively high-dose procedure which use has been rapidly increasing in many countries, although a decline has been observed recently in some developed countries. Relatively little is known about CT usage in Brazil. A recent report showed that number of CT procedures among outpatients of the Brazilian public healthcare system (SUS) tripled from 2001 to 2011 and about 13% of all CTs procedures were underwent among pediatric and young adult patients. In the present study, we aimed to evaluate CT use in the private healthcare system, where the larger availability of CT scanners may result in a different CT usage pattern. We evaluated data from 15,892 CT procedures underwent by children and young adults (<20 years) between 2005 and 2015 in a private general hospital in the city of Rio de Janeiro. These procedures represented about 8% of the overall number of CT scans in the hospital over the study period. The number of CT examinations increased 10% per year, from 902 in 2005 to 2,376 in 2015. Head/neck was the most frequently examined body anatomical region for all age groups, except for patients aged 15-19 years for whom abdomen/pelvis was the most common scanned region. One third of the patients underwent more than one CT examination in the hospital during the study period, with multiple CT exams increasing with patient age. The greater availability of other diagnostic imaging examinations in the private setting, such as magnetic resonance and ultrasound, could have contributed to the lower proportion of pediatric and young adult CT in the study hospital. The rapid increase of pediatric CT usage in the public and private healthcare setting reinforces the need for initiatives to avoid unwarranted CT exposure in Brazil.